2009
DOI: 10.1016/j.apmr.2009.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Patient Motivation and Adherence to Postsurgery Rehabilitation Exercise Recommendations: The Influence of Physiotherapists' Autonomy-Supportive Behaviors

Abstract: These preliminary findings are promising and provide an empirical basis for further research to test the efficacy of autonomy support training designed to increase patients' rehabilitation adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
163
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(180 citation statements)
references
References 27 publications
14
163
1
2
Order By: Relevance
“…2016; 9(3):e6494. 5 (15). These researchers used a method called "supportive independent behaviors" to achieve optimal adherence in the area of motor activity after surgery; so by presenting simple and understandable training to the patients and their families, the rate of adherence to the treatment program increased significantly in the group that had used this method (16).…”
Section: Total Adherencementioning
confidence: 99%
“…2016; 9(3):e6494. 5 (15). These researchers used a method called "supportive independent behaviors" to achieve optimal adherence in the area of motor activity after surgery; so by presenting simple and understandable training to the patients and their families, the rate of adherence to the treatment program increased significantly in the group that had used this method (16).…”
Section: Total Adherencementioning
confidence: 99%
“…Increasing evidence shows that the nature of the therapeutic relationship between the physiotherapist and the patient influences treatment adherence and clinical outcomes (24). Adherence is greater when practitioners are perceived as supportive rather than paternalistic (25). A recent meta-analysis (26) showed that effective communication and support from practitioners is vital to promote patients' self-belief with regard to exercise and long-term motivation.…”
mentioning
confidence: 99%
“… Four studies assessed other than physical activities in rehabilitation (Ashe, Eng, Miller, & Soon, 2007;Battersby et al, 2009;Kayes et al, 2010;Post et al, 2012)  Three studies dealt with therapeutic sessions (Chan, Lonsdale, Ho, Yung, & Chan, 2009;Logsdon, McCurry, Pike, & Teri, 2009;Saltapidas & Ponsford, 2007)  Three articles contained incomplete (Lenze, Munin, Dew, et al, 2004) or no data (Lequerica, 2005;Lequerica, Donnell, & Tate, 2009) …”
Section: Figure 1: Search Strategymentioning
confidence: 99%